PENGISTILAHAN DISABILITAS DALAM BAHASA ARAB - Anshari, Muhammad; Mahridawati, Mahridawati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
This study discusses the use of terms related to disability in Arabic. This research aims to see the most popular, dominant, and most widely used terms in Arabic in academic texts and Islamic books. Online data and several references (books, magazines, and others) are the data sources in this study. The term al muʿawwaq/almuʿawwaqīn/i'aqah is the most popular, dominant, and referenced term in terms of persons with disabilities compared to some terms dhawī al iḥtiyājāt al khāssa, al fiʾāt al khāssa, al afrād ghayr al ʿādiyyīn and dhawī al a'hat, this is the result of this research. Each term represents the point of view and perspective used to see the disability issues, the term dhawī al a'hat represents a medical perspective, the term al afrād ghayr al ʿādiyyīn represents a moral perspective, dhawī al iḥtiyājāt al khāssa, and al muʿawaqah represent perspectives social. Terms that represent the social model and individual/medical are more often referred to and used in some terms and are very popular in academic texts, Islamic literature, regulations, and in the digital world such as news, web, images, and Youtube.Keywords: Dhawī al iḥtiyājāt al khāssa, al fiʾāt al khāssa, al afrād ghayr al ʿādiyyīn and dhawī al a'hat